Perlindungan Hukum Terhadap Informasi Iklan Yang Menyesatkan - Wahyu Prabowo; Kurnia Tri Latifa; Rr Yunita Puspandari (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
This study aims to examine the existence of misleading advertising information reviewed from the law perspective as well as the role of the government in providing legal protection to consumers. This study implemented conceptual and legal approaches. The results of the research show that advertisement is stated to be misleading if it violates Article 9 of The Consumer Protection (UUPK). As for the legal consequences, the advertisment’s owners may be subject to administrative, criminal, civil, and additional penalties. Consumers who suffer from misleading advertising information receive preventive legal protection in the form of making legal rules that guarantee legal protection and supervision of customers. In addition, consumers also get repressive legal protection through the courts of the justice so that costumers can file claims to the court or through channels outside the court thant are managed by The Consumer Dispute Settlement Board (BPSK). Based on the research results, its concluded that forms of misleading advertisements are misleading, deceptive, omission, and puffery. Businesses that are dishonest in advertising their products will be subject to sanctions. The advertising legal protection is contained in the UUPK, KUHPer, and the 2020’s Amendment of Indonesian Pariwara Ethics.